Climate smart agriculture and food systems that reduce poverty and hunger - Babu, Suresh Chandra (Organization for Economic Cooperation and Development, 2024)
Poor communities that rely on functioning food systems for their livelihoods are highly vulnerable to the devastating effects of climate change while agri-food systems are significant emitters of greenhouse gases. This chapter reviews opportunities to scale up innovative technology and practices to transform food systems and to leverage climate action to reduce poverty, hunger and malnutrition in line with the complementary Sustainable Development Goals. Drawing on country experiences – India, Tajikistan, Lao People’s Democratic Republic and Myanmar – with integrated strategies, it looks at how climate strategies such as nationally determined contributions can be aligned with national agricultural and antipoverty strategies; the need for multisector and multistakeholder action and participation; challenges to joint financing for climate action, poverty and hunger goals; and adapting government and donor systems to co-ordinate implementation.